(untitled) - Pastor-Satorras, Romualdo (Cambridge, UK, 2004)
Viewed in this analysis from a statistical physics perspective, the Internet is perceived as a developing system that evolves through the addition and removal of nodes and links. This perspective permits the authors to outline the dynamical theory that can appropriately describe the Internet's macroscopic evolution. The presence of such a theoretical framework will provide a revolutionary way of enhancing the reader's understanding of the Internet's varied network processes.
Keywords: Internet,Vật lý thống kê,Statistical physics,Internet